EVALUATION OF LEADERSHIP AND PERSONAL SKILLS IN ENGINEERING-INFORMATICS STUDENTS AT STIKOM PGRI BANYUWANGI : EVALUASI KETERAMPILAN KEPEMIMPINAN DAN KETERAMPILAN PERSONAL PADA MAHASISWA TEKNIK INFORMATIKA DI STIKOM PGRI BANYUWANGI - Mohamad Dedi (SOSIOEDUKASI, 2023)
Along with the increasing need for competent human resources in the information technology industry which continues to develop dynamically, Higher Education Institutions have a crucial role in formulating curricula that can answer these needs. The leadership function becomes an important parameter in moving the organization so that it can run according to plan. In its implementation, Leadership courses and personal skills are needed in an engineering profession that utilizes a wide range of disciplinary knowledge. The purpose of this study was to obtain an overview of the evaluation of the learning outcomes of Leadership and Personal skills in 49 students of the Informatics Engineering study program at the PGRI Banyuwangi College of Communication Sciences (STIKOM). This research was conducted in stages including planning, action, observation, & evaluation. The results of implementation and direct observation are supplemented by documentation and analyzed qualitatively. The evaluation results show that the level of ability of the respondents tends to increase in cycles I to II with good qualifications. The conclusion of the research shows that the respondents' awareness of the importance of leadership courses and personal skills in managerial issues, innovative products, and success metrics is formed